2014
DOI: 10.1371/journal.pone.0080398
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes by Mode of Assisted Conception and Sub-Fertility in an Australian Data Linkage Cohort

Abstract: BackgroundFertility treatment is associated with increased risk of major birth defects, which varies between in vitro fertilisation (IVF) and intracytoplasmic sperm injection (ICSI), and is significantly reduced by embryo freezing. We therefore examined a range of additional perinatal outcomes for these exposures.MethodsAll patients in South Australia receiving assisted conception between Jan 1986–Dec 2002 were linked to the state-wide perinatal collection (all births/stillbirths ≥20 weeks gestation or 400 g b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
125
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 41 publications
(50 reference statements)
12
125
1
7
Order By: Relevance
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
“…Prior studies have also consistently reported an excess of large-for-gestational age (LGA) birthweights among children born from frozen embryos; [4][5][6][7][8][9][10][11][12] longer embryo culture of fresh embryos has also been implicated as a potential cause of LGA [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that singletons born after FET have a perinatal outcome more comparable to those born after natural conception than to those born after fresh embryo transfer (fresh ET), having higher birth weight and less pregnancy complications [2][3][4][5][6][7][8][9][10]. However, higher risk for birth of a singleton being large for gestational age (LGA) has been revealed after FET [2,3,7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The influences of the culture media [21][22][23], culture period [24,25], hormonal protocols [26], and infertility [12,14,27] on the IVF singleton birth weight have already been considered. There are several studies confirming that IVF placentas differ from spontaneous placentas in their size, shape, weight, and abnormality rate [3,6,7,[28][29][30][31], and that placentation following FET differ from the placentation following fresh ET [3,6,7,13] In this study, we analyzed the connection of IVF procedure type and maternal background factors to LGA risk.…”
Section: Introductionmentioning
confidence: 99%